Shrimp Product Innovation in Smart Fisheries Village Kombading, Jembrana, Bali - Anis Khairunnisa; I Gusti Ayu Budiadnyani; Siluh Putu Sri Dia Utari; Desy Febrianti; Iftachul Farida; Ika Astiana; Pinky Natalia Samanta; Resti Nurmala Dewi; Fenny Crista Anastasia Panjaitan; Mahaldika Cesrany; Medal Lintas Perceka; Made Tisna Adhi Bharata; Ni Made Anggun Pradnyani Putri (Universitas Muhammadiyah Palembang, 2023)
Kombading village is Smart Fisheries Village (SFV) area from Shrimp Cluster of Devisa Village under Jembrana Marine and Fisheries Polytechnic and Indonesian Export Financing Institute Denpasar guidance. This technical guidance aims to supporting one of SFV concept development as priority program of Blue Economy based by Ministry of Marine and Fisheries. The technical guidance attended by 20 participants from Processing and Marketing groups of Mina Jaya Pertiwi (10 person) and teachers-parent of Early Childhood Education School Darul Ulum Kombading. There are 3 substances was given to participants i.e. (1) benefits of consuming the fish product, (2) shrimp products diversification (crispy shrimp head, fried shrimp meatball, and shrimp head broth powder), and (3) introduction of PIRT Certification for home industry products. Sensory evaluation shows that crispy shrimp head and fried shrimp meatball needs improvement in texture and appearance. Moreover, this technical guidance was able to increase participants knowledge significantly (p<0,05).